Texts Complying with Societal Pressures : Changing Genres in Finnish Companies’ CSR Reporting - Koskela, Merja; Enell-Nilsson, Mona; Hjerppe, Cecilia (Palgrave Macmillan, 2023)
Drawing from the Nordic tradition of sakprosa research, this chapter aims at analysing how generic and intertextual resources are used in Finnish companies’ corporate social responsibility (CSR) reporting. Longitudinally, we study the reporting format, that is, whether the companies are reporting about their sustainability issues separately or as part of their annual report. A comparable synchronic approach is applied to intertextuality between reports and sustainability pages on corporate websites. The data stems from companies listed in the Nasdaq Helsinki Stock Exchange (OMX25 index). It comprises CSR reporting from the financial years 2016–2020 and sustainability pages of three companies. The study shows a tendency of keeping the chosen reporting format irrespective of its kind. However, two types of variability occur: selective variability referring to one format change in the investigated time span, and hybridity, combining features of different formats. Three intertextual strategies between the texts of reports and web pages were detected: convergence, adaptation, and divergence. Our results show how choices of reporting format and intertextual strategies are governed by the company context and practices, and also by governance issues and regulation. In this way, the complexity of text-society relationships as postulated by sakprosa research is illustrated in the context of business texts.
Keywords: fi=Markkinointi|en=Marketing|; fi=Viestintätieteet|en=Communication Studies|